Miejski Komitet Wychowania Fizycznego i Przysposobienia Wojskowego w Tomaszowie Mazowieckim w latach Drugiej Rzeczypospolitej - Jarno, Witold (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2015)
The article describes the history of the Municipal Committee of Physical Education and Military Training in Tomaszow Mazowiecki. This Committee was created in 1927 and functioned until the outbreak of the Second World War in 1939. The committee consisted of representatives of local authorities, associations and industrialists. Chairman of the committee was every time the mayor. The task of the committee was coordinating and supporting the activities of local authorities and social associations in the development of sports and military training among school children. Education had a positive impact on preparing young people for military service, raising the level of physical fitness and civic awareness. With the committee cooperated almost all the local organizations and associations engaged in education of school youth.